Non-Hodgkins lymphoma of bilateral eyelids with basal cell carcinoma of nose: a rare case report - Swer, Dorafiona; Mahawar, Rahul; Sobita Devi, Yumkhaibam; Sangtam, Dangtila (International Journal of Research in Medical Sciences, 2024)
Malignant tumours affecting the eyelid mainly include basal cell carcinoma. Non-Hodgkin’s lymphoma may occur in almost any part of the body and should be considered in the differential diagnosis of extra lymphoid tumours. Non- Hodgkin’s lymphoma of the eyelid is rare. Rare diseases should be considered in differential diagnoses because they have the tendency for rapid systemic involvement and they may require treatments that are different from the other common diseases. Basal cell carcinoma occurs most frequently at sun-exposed sites, most commonly in the head and neck regions. The aim of any therapy selected for BCC treatment involving the head and neck is to ensure complete removal, functional preservation, and a good cosmetic outcome. Here, we reported a case of a 70-year-old female with non-Hodgkin lymphoma of eyelids followed by basal cell carcinoma of the nose treated with multimodality approach.